2003
DOI: 10.1104/pp.102.019398
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Assessment of Altered Expression of Hsc70-1 in Arabidopsis. Evidence for Pleiotropic Consequences

Abstract: Hsp70s function as molecular chaperones. The protective chaperone activities of hsp70 help to confer tolerance to heat, glucose deprivation, and drought. Overexpression of hsp70s in many organisms correlates with enhanced thermotolerance, altered growth, and development. To better understand the roles of hsp70 proteins in Arabidopsis, the molecular and physiological consequences of altered expression of the major heat shock cognate, Hsc70-1, were analyzed. Extensive efforts to achieve underexpression of Hsc70-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
146
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 45 publications
5
146
0
Order By: Relevance
“…AtHsfA3 is a member of the HSF gene family, which consists of 21 genes belonging to three major classes that are based on structural differences, HsfA, HsfB, and HsfC. HsfAs, have been shown to be the major transcription factors that function in heat-induced expression of HSP genes (24). AtHsfA3 might act as a transcription factor in HS-stress-responsive gene expression, but detailed function of AtHsfA3 has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AtHsfA3 is a member of the HSF gene family, which consists of 21 genes belonging to three major classes that are based on structural differences, HsfA, HsfB, and HsfC. HsfAs, have been shown to be the major transcription factors that function in heat-induced expression of HSP genes (24). AtHsfA3 might act as a transcription factor in HS-stress-responsive gene expression, but detailed function of AtHsfA3 has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of some HSP genes is reported to be induced not only by HS but also by drought stress (22). HSPs act as molecular chaperones by maintaining homeostasis of protein folding and thus help to maintain the metabolic and structural integrity of cells (22)(23)(24). HSP expression is regulated at the transcriptional level by HS transcription factors (HSFs), which recognize the conserved HS element in the promoter regions of HSP genes (24)(25)(26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the four other cytosolic Hsc70 isoforms exhibited increased transcript levels, albeit to a lesser extent ( Figure 2B). Previous studies have shown that Hsc70-1 mediates heat tolerance, plant development, immune response, abiotic stress response, and protein targeting to the nuclear envelope membrane (Sung and Guy, 2003;Noë l et al, 2007;Brkljacic et al, 2009;Cazalé et al, 2009). Thus, each cytosolic Hsc70 isoform may have a specific function, with a degree of functional redundancy among the isoforms (Noë l et al, 2007).…”
Section: Chloroplast Proteins In Ppi2 Mutant Plants Are Degraded By Tmentioning
confidence: 99%
“…Whereas DnaK system efficiently solubilized and refolded small protein aggregates (Diamant et al 2000), large protein aggregates are solubilized in concert with Hsp100/ ClpB (Diamant et al 2000;Acebron et al 2009). Expression of cytosolic Hsp70 genes is linked to acquired thermotolerance because of their property to reactivate the protein aggregates formed under various stress conditions (Lee and Schoffl 1996;Yang et al 2009;Qi et al 2011;Zhou et al 2012;Sung and Guy 2003). It is noted that Hsp70 may function as a negative feedback regulator of HSF activity (Shi et al 1998;Kim and Schoffl 2002).…”
Section: Introductionmentioning
confidence: 99%